Disentangling specific and unspecific components of innate immune memory in a copepod–tapeworm system - Ng, Tze Hann; Harrison, Mark C.; Scharsack, Jörn P.; Kurtz, Joachim (Frontiers in Immunology, 2024)
Evidence that the innate immune system can respond with forms of memory upon reinfection has been accumulating over the past few years. These phenomena of ‘immune priming’ in invertebrates, and ‘trained immunity’ in vertebrates, are contrary to previous belief that immune memory and specificity are restricted to the adaptive immune system. However, while trained immunity is usually a response with rather low specificity, immune priming has shown highly specific responses in certain species. To date, it is largely unknown, how specificity in innate immune memory can be achieved in response to different parasite types. Here, we re-visited a system where an exceptionally high degree of innate immune specificity had been demonstrated for the first time, consisting of the copepod Macrocyclops albidus and its natural parasite, the tapeworm Schistocephalus solidus. Using homologous (same family) vs. heterologous (different family) priming-challenge experiments, we first confirm that copepods exposed to the same parasite family benefit from reduced secondary infections. We further focussed on exposed-but-not-infected copepods in primary exposure to employ a transcriptomic approach, distinguishing between immunity that was either specific or unspecific regarding the discrimination between tapeworm types. A weighted gene co‑expression network (WGCN) revealed differences between specific and unspecific immunity; while both involved histone modification regulation, specific immunity involved gene-splicing factors, whereas unspecific immunity was primarily involved in metabolic shift. We found a functional enrichment in spliceosome in specific immunity, whereas oxidative phosphorylation and carbon metabolism were enriched in unspecific immunity. Our findings allow for discrimination of specific and unspecific components of an innate immune memory, based on gene expression networks, and deepen our understanding of basic aspects of immune systems.